Effect of Palm Oil Fuel Ash as Partial Cement Replacement on Strength of Foamed Palm Oil Clinker Concrete - Muhammad Hariz, Mohamed Idris; Khairunisa, Muthusamy; Rokiah, Othman (Universiti Malaysia Pahang, 2016)
Malaysia, being one of the largest palm oil producer in the world generates increasing amount of by-products namely palm oil clinker and palm oil fuel ash which usually dumped as environmental polluting waste. At the same time, increasing sand mining activities to meet the need of construction industry has arisen the concern of researchers on the negative impact of the activity towards environment when it is carried excessively. With the aiming these problems,researcher has looked into the possibilities of producing foamed palm oil clinker concrete containing palm oil fuel ash as a supplementary admixture. The present research investigates the strength performance of foamed palm oil clinker concrete when palm oil fuel ash is added as partial cement replacement. All specimens were cast in form of cubes and then subjected to continuous water curing. The compressive strength test was carried out at 7 and 28 days. The findings show that the strength performance of foamed palm oil clinker concrete is influenced by amount of palm oil fuel ash integrated in the mix. Addition of palm oil fuel ash at 10% successfully enhances the compressive strength of the lightweight concrete. Integration of solid wastes from palm oil industry in foamed concrete production would contribute towards a more environmental friendly palm oil industry and able to provide the contractors with locally made sustainable lightweight construction material.